2017
DOI: 10.23937/2474-3658/1510034
|View full text |Cite
|
Sign up to set email alerts
|

Needlestick Injury among Medical Students in an Australian University

Abstract: Needlestick Injuries (NSI) commonly occurs in the hospital setting. Medical students are at risk of NSI due to lack of clinical experience. The purpose of this study was to investigate the incidence and knowledge, attitudes, awareness and practices of NSI among medical students at an Australian university. We conducted a cross-sectional study using an online questionnaire on NSI-related knowledge, attitude, awareness, practice, incidents and follow up. The survey was distributed to clinical students (years 3-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…This indicates the importance of the integration of infection control guidelines into the curriculum of nursing and paramedical students and the emphasis on its practice in the areas of clinical training. This study is in line with the results of Marjadi et. al.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates the importance of the integration of infection control guidelines into the curriculum of nursing and paramedical students and the emphasis on its practice in the areas of clinical training. This study is in line with the results of Marjadi et. al.…”
Section: Discussionsupporting
confidence: 94%
“…(2017) who found that respondents' NSI-related knowledge were generally moderate with a median score of 3 out of a maximum of 6 for knowledge. [23] This consistency of findings despite the advancement in the infection control programs is alerting. Clinical instructors should increase students' training to assess clinical tasks and identify NSI risks that they will face.…”
Section: Discussionmentioning
confidence: 95%
“…A total of 10,233 healthcare workers were included in 18 studies, of which were conducted in 14 countries [ 16 , 25 – 41 ]: three articles [ 29 , 33 , 41 ] in Iran, two in Ethiopia [ 27 , 36 ], two in India [ 28 , 39 ], and one (5.55%) in other countries such as Nigeria [ 30 ], USA [ 25 ], China [ 31 ], Serbia [ 26 ], Saudi Arabia [ 32 ], Bangalore [ 34 ], Thailand [ 16 ], Australia [ 35 ], Bosnia and Herzegovina [ 37 ], Tanzania [ 38 ], and Switzerland [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the included articles, 6 articles [ 26 – 30 , 33 ] reported both prevalence of NSIs in career time and previous one year, while 6 [ 25 , 31 , 32 , 36 , 37 , 41 ] and 6 [ 16 , 34 , 35 , 38 – 40 ] of articles reported career time alone and previous one-year prevalence of NSIs alone, respectively. Most ( 5 (83.3%)) of the included articles [ 16 , 26 – 34 , 36 39 , 41 ] were conducted in the developing countries, while the rest of the studies [ 25 , 35 , 40 ] were in a developed country ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only a minor proportion of respondents reported fear of stigma and discrimination as a cause of non-reporting (11%), whereas this formed the main cause of non-reporting in other studies. [28] The KAP regarding NSI and PEP among HCWs is also relevant among the primary care physicians as they provide the bulk of medical services to a good majority of patients. Their job responsibilities include phlebotomy, block anesthesia, IV cannulation, laceration repair, etc., which makes them at risk for NSI.…”
Section: Discussionmentioning
confidence: 99%